2012
DOI: 10.3748/wjg.v18.i40.5759
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status in relation to lifestyle in patients with compensated viral cirrhosis

Abstract: Non-hospitalized cirrhotic patients may need to maintain an adequate dietary intake and receive lifestyle guidance to increase their physical activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
2
25
1
1
Order By: Relevance
“…Compared with daily steps in other chronic diseases, shown for reference in Fig. , our patients' mean activity level was similar to that of persons with dialysis‐dependent chronic renal failure and chronic obstructive pulmonary disease (COPD) and less than that of patients with congestive heart failure (CHF) or compensated hepatitis C cirrhosis …”
Section: Resultssupporting
confidence: 49%
“…Compared with daily steps in other chronic diseases, shown for reference in Fig. , our patients' mean activity level was similar to that of persons with dialysis‐dependent chronic renal failure and chronic obstructive pulmonary disease (COPD) and less than that of patients with congestive heart failure (CHF) or compensated hepatitis C cirrhosis …”
Section: Resultssupporting
confidence: 49%
“…This suggests that liver cirrhosis can induce muscle injury. Previously, we found that skeletal muscle mass and muscle strength assessed anthropometrically were significantly lower in patients with chronic liver disease than in healthy subjects . Moreover, the amount of exercise, expressed as active physical activity measured using an accelerometer, was significantly lower in cirrhotic patients with sarcopenia than in cirrhotic patients without sarcopenia .…”
Section: Discussionmentioning
confidence: 82%
“…Previously, we found that skeletal muscle mass and muscle strength assessed anthropometrically were significantly lower in patients with chronic liver disease than in healthy subjects. 59 Moreover, the amount of exercise, expressed as active physical activity measured using an accelerometer, was significantly lower in cirrhotic patients with sarcopenia than in cirrhotic patients without sarcopenia. 16 The results of these studies suggest that patients with chronic liver disease and loss of skeletal muscle have decreased exercise tolerance, possibly indicating that the reduction in physical activity may be a factor leading to the loss of skeletal muscle.…”
Section: Discussionmentioning
confidence: 95%
“…In the present analysis, a finger‐circle test result other than Bigger in male patients and Smaller in female patients predicted early occurrence of MA. Daily physical activity has been reported to be lower in CLD patients as compared with healthy subjects . To confirm the relationships among total muscle volume or area of L3, maximum calf circumference, and level of daily physical activity, an additional study is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Daily physical activity has been reported to be lower in CLD patients as compared with healthy subjects. 18,19 To confirm the relationships among total muscle volume or area of L3, maximum calf circumference, and level of daily physical activity, an additional study is necessary. In addition, number of obese individuals was too small in the present cohort (3.4%) for confirming the predictive value of finger-circle test in obese individuals with CLD.…”
Section: Discussionmentioning
confidence: 99%